2016
DOI: 10.1186/s12889-016-2996-y
|View full text |Cite
|
Sign up to set email alerts
|

Testing the price and affordability of healthy and current (unhealthy) diets and the potential impacts of policy change in Australia

Abstract: BackgroundPrice and affordability of foods are important determinants of health. Targeted food pricing policies may help improve population diets. However, methods producing comparable data to inform relevant policy decisions are lacking in Australia and globally. The objective was to develop and pilot standardised methods to assess the price, relative price and affordability of healthy (recommended) and current (unhealthy) diets and test impacts of a potential policy change.MethodsMethods followed the optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
143
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(158 citation statements)
references
References 24 publications
(49 reference statements)
13
143
0
2
Order By: Relevance
“…It showed that healthy diets were 12% cheaper than less healthy diets for an average family. 22 Finally, data from our evidence reviews on chronic disease prevention interventions in children and young adults, and on the costs and benefits of urban form on health, have been used in the National Strategic Framework for Chronic Conditions, and NSW Ministry of Health urban planning with local districts, respectively. These all highlight early examples of the Prevention Centre's research being relevant and useful.…”
Section: Different Ways Of Working Results In Unique Outcomesmentioning
confidence: 99%
“…It showed that healthy diets were 12% cheaper than less healthy diets for an average family. 22 Finally, data from our evidence reviews on chronic disease prevention interventions in children and young adults, and on the costs and benefits of urban form on health, have been used in the National Strategic Framework for Chronic Conditions, and NSW Ministry of Health urban planning with local districts, respectively. These all highlight early examples of the Prevention Centre's research being relevant and useful.…”
Section: Different Ways Of Working Results In Unique Outcomesmentioning
confidence: 99%
“…The results of that pilot suggested that healthy diets can be more affordable than the current Australian diet, particularly because people currently spend a relatively large proportion of their household budget on alcohol and discretionary foods (a family of two adults and two children was found to spend over 58 % of its food dollars on discretionary choices). Nevertheless, the individual prices of some healthy foods, particularly meat, dairy and vegetables, were found to be relatively expensive compared with energy-dense discretionary foods (8) . Also, the study found that while a diet consistent with dietary guidelines was affordable for families on a median income (18 % of disposable income), it was less affordable for low-income families (28 % of their household disposable income) (8) .…”
mentioning
confidence: 99%
“…Nevertheless, the individual prices of some healthy foods, particularly meat, dairy and vegetables, were found to be relatively expensive compared with energy-dense discretionary foods (8) . Also, the study found that while a diet consistent with dietary guidelines was affordable for families on a median income (18 % of disposable income), it was less affordable for low-income families (28 % of their household disposable income) (8) . Another remarkable finding from the systematic review featured in this issue (6) was that ten of eleven identified 'healthy basket' food pricing tools did not fully align with the principles of the most recent Australian Dietary Guidelines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…28 A recent study looked at the impacts of GST changes on the affordability of two theoretical diets, healthy and current (unhealthy), and used food costs from stores in two locations in Queensland. 14 The healthy diet basket was modelled against the Australian Dietary Guidelines with the foods chosen indicative of the minimum requirements to meet dietary guidelines rather than a real world meals-based menu plan. However, to date, there has been no modelling of the potential impacts of changes to the GST on food affordability, with food prices collected in-store from a representative sample of Australian supermarkets.…”
mentioning
confidence: 99%